Assessing the Remote Engineering Lab VISIR at Al-Quds University in Palestine - Odeh, Salaheddin (2017)
Engineering labs play a vital role in engineering education, make science come alive, and supply students with better understanding of theories. As a result, they contribute to the improvement of their knowledge and skills. Remote labs not enable sharing of teaching resources such as devices, equipment and instrumentation between universities, but also relax time and space constraints; yet they are considered as a complementary asset to the traditional hands-on labs. This paper is concerned with a two-stage assessment of the engineering remote lab VISIR. In the first stage, the assessment investigated if the students accept to use VISIR in their future lab courses at the Faculty of Engineering at Al-Quds University in Palestine. In the second stage, a deeper analysis will be performed to compare VISIR to hands-on and simulators based on the evaluation criteria: performance, students’ retention rate and satisfaction survey.